2022
DOI: 10.1002/alz.12670
|View full text |Cite
|
Sign up to set email alerts
|

High lifelong cognitive reserve prolongs disability‐free survival: The role of cognitive function

Abstract: Introduction:The association between cognitive reserve (CR) and survival with independence is unknown. We examined whether lifelong CR accumulation is associated with disability-free survival and explored the extent to which cognitive function mediates this association.Methods: Within the Rush Memory and Aging Project, 1633 dementia-and disabilityfree participants were followed annually for up to 22 years. Lifelong CR including education, early-/mid-/late-life cognitive activities, and late-life social activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Examples of existing theoretical frameworks that may be salient at that point and may help to inform a theoretical framework for ELs include Cognitive Reserve Theory and the Delirium Systems Integration Theory 45,46 . Both theories attempt to explain the mechanisms by which cognitive function varies across individuals (cognitive reserve) and within individuals (delirium systems integration) over time 45–47 . These other theoretical perspectives, however, are broad in scope and perspective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of existing theoretical frameworks that may be salient at that point and may help to inform a theoretical framework for ELs include Cognitive Reserve Theory and the Delirium Systems Integration Theory 45,46 . Both theories attempt to explain the mechanisms by which cognitive function varies across individuals (cognitive reserve) and within individuals (delirium systems integration) over time 45–47 . These other theoretical perspectives, however, are broad in scope and perspective.…”
Section: Introductionmentioning
confidence: 99%
“… 45 , 46 Both theories attempt to explain the mechanisms by which cognitive function varies across individuals (cognitive reserve) and within individuals (delirium systems integration) over time. 45 , 46 , 47 These other theoretical perspectives, however, are broad in scope and perspective. On the contrary, the proposed preliminary framework is narrowly focused on specifying how lucidity is operationalized.…”
Section: Introductionmentioning
confidence: 99%
“…All participants provided written informed consent and repository consent to allow sharing of their data. 19…”
Section: Methodsmentioning
confidence: 99%
“…MRI has been widely applied to examine structural brain changes and can provide insight into the pathophysiology underlying changes in cognition. 14 Previous neuroimaging studies reported an association between motor function and reduced gray matter, white matter, and hippocampal volumes, [15][16][17][18][19] though other studies produced conflicting results. 15,16 So far, few studies have systematically addressed the association between motor function and domain-specific cognitive trajectories and brain structural measures assessed by MRI scans.…”
Section: Introductionmentioning
confidence: 99%
“…Higher CR reduces the prevalence of dementia, bringing down public costs related to care (Zissimopoulos et al, 2015). At the individual level, this corresponds to fewer years of disability and patient dependence (Li et al, 2022) and yields important practical implications for prevention and cure policies for neurodegenerative diseases (Wu et al, 2016). CR can only be indirectly measured, using socio‐behavioural proxies (Stern et al, 2020), which share an underlying process and each adds a unique contribution to CR (Opdebeeck et al, 2016).…”
Section: Introductionmentioning
confidence: 99%